Dietary intake in elite female and male field hockey players - Torres Garcia, A.; Garcia Aparicio, A.; Alonso Ojembarrena, M.; Garrido Pastor, G. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Field hockey is a team sport that requires varying levels of intensity (high, medium and low). Matches are 90 minutes in length. During this time, player substitutions are continuous and unrestricted, so players participate at high intensity levels of exercise throughout a match. In these athletes, body composition is not a primary area of concern. However, to compensate for the high metabolic energy demands, dietary intake is very important. Dietary habits were analyzed in young elite female and male field hockey players. The goal of this study was to compare (female versus male) nutritional patterns in these players and to advice them on healthy and optimal dietary intake. Methods Subjects were 12 Spanish young elite female field hockey players (F) calibre age=20.5±2.2yr; ht=162.9±3.3cm; wt=59.2±3.4kg; BMI=22.3±3.1kg/m2 and 12 Spanish young elite male field hockey players (M) calibre age=20.1±2.0yr; ht=175.8±6.4cm; wt=71.1±7.5kg; BMI=23.0±1.1kg/m2 Diet composition was estimated by food weighing (Mettler Toledo scale with 1g accuracy) for a 5 day period. During the same days they completed a 24h activity questionnaire to provide energy expenditure estimation (EER)(1). Results Energy intake (EI) and EER values were similar in both groups (F and M), meaning that both achieved energy balance. However, in F, lower EER (kcal/d), [2256±203 vs. 3094±446 in M (p<.001)], and EI (kcal/d), [2200±250 vs. 2924±656 (p<.01)] were found, specifically EI (kcal) from lunch (p<.001) and dinner (p<.01) was higher in M. Energy distribution or percentage of energy (% E) derived from macronutrients revealed that % of E from protein was similar in F and M, but differences were found in carbohydrates (higher in F, p<.05) and fats (lower in F, p<.01). Total fat (g) (71.4±14.3 vs. 115.4±26.9 [p<.001]), saturated (g) (19.9±3.9 vs. 33.7±10.5 [p<.001]), monounsaturated (g) (28.7±7.0 vs. 45.1±8.9 [p<.001]) and cholesterol (mg) (357±236 vs. 472±172) intakes were significantly higher in M. Conversely, M demonstrated lower fibre intake (29.9±2.6 vs. 20.2±7.4 [p<.05]). We found inadequate intakes with respect to the recommendations (1) for: calcium (F), magnesium (M), potassium (F, M), vitamin E (F, M) and folate (M). Discussion/Conclusion Energy distribution and several micronutrient intake values were suboptimal, especially in M hockey players. In both F and M, marginal intakes of some micronutrients and fibre were associated with poor intake of vegetable food group servings. High cholesterol and fat intakes were related to an excess of animal food group servings. More in-depth nutritional strategies are recommended, including a closer relationship between nutritionists and athletes, to effect changes in diet quality.